Molten Salt Reactor Technology: Progress, Challenges, and Prospects - Fan ZHANG; Bolong GUO (南方能源建设)
[Objective] The study aims to comprehensively and systematically explore the current development status of molten salt reactor (MSR) technology, clarify the advantages of MSR as the fourth-generation nuclear power technology, and analyze the major challenges facing its commercialization. By analyzing the development history, technical classification, and research and development progress in various countries, the study provides valuable references for the future development of MSR technology. [Method] Using the research methods of literature review and comparative analysis, the development history of MSR technology was reviewed, the different types of MSR technology were classified in detail, and the latest progress in MSR technology research and development in countries such as the United States, China, Russia, France, and Canada was deeply analyzed. Meanwhile, based on actual cases such as the MSRE experimental reactor and the TMSR project, the key technical progress and major challenges of MSR technology were discussed. In addition, the impact of international cooperation and technological innovation on the development of MSR technology was also analyzed. [Result] It is found that MSR technology has been widely concerned globally due to its advantages of high safety and high fuel utilization rate. The United States has verified the engineering feasibility of MSR through the MSRE experimental reactor, and China has made important progress in molten salt preparation and purification in the TMSR project. Russia, France, Canada, and other countries have also made significant achievements in the field of MSR technology. However, the commercialization of MSR technology still faces many challenges, including supply chain construction, fuel supply, regulatory framework adaptation, waste treatment, safety assurance measures, and complex maintenance and operation. [Conclusion] Although MSR technology faces many challenges, its advantages in safety, fuel utilization rate, and design flexibility give it broad development prospects. International cooperation and technological innovation are key factors in promoting the progress of MSR technology. With the continuous advancement of related technologies, these challenges are gradually being resolved. In the future, MSR technology is expected to become an important support for the global energy structure transformation, playing a crucial role in improving fuel utilization, reducing nuclear waste generation, and enhancing reactor safety. As research deepens and technology matures, MSR technology is expected to achieve commercialization and contribute to the global clean energy transition.